(untitled) (Geographical Journal of Nepal, 2019)
Eastern Uttar Pradesh has a number of mills including large as well as small and ancillaries units because of availability of sufficient amount of sugarcane in this area. It has fertile plain which is highly suitable for cultivation of sugarcane, but many factors related to sugarcane cultivation as well as sugar mills have pushed the sugar industry to be agglomerated at some places which ultimately brought regional variation in distribution patterns and grouped in some clusters. This paper analyses the distribution pattern and clustering of sugar industry in eastern Uttar Pradesh. The study is based on primary as well as secondary data including number of industrial units, capital investment and involved employment. Out of total 30 working mills, 25 mills make clusters occupying eight districts, i.e., Kushinagar, Deoria, Gorakhpur, Mahrajganj and Bahraich, Balrampur, Gonda, Basti. These clusters are located in the Saryupar plain as well as Tarai region which show that sugar industry is exclusively developed in intensive sugarcane production areas.